Common Fixed Points of Compatible Mappings - Singh, M. P.; Yumnam, R. (Journal of Scientific Research, 2012)
In this paper we prove two common fixed point theorems by considering four mappings in complete metric space. In the first theorem we consider two pairs of compatible mappings of type (A) and in the second theorem we consider two pairs of compatible mappings of type (B). Our results modify and extend some earlier results in the literature. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10567 J. Sci. Res. 4 (3), 603-608 (2012)